KAJIAN HUKUM PEMANFAATAN DANA DESA DALAM PEMANFAATAN DANA DESA RANAH DESA PILOT DI DESA PONGGOK, POLANHARJO KLATEN - WIDAYATI, MM. SRI (Dinamika Hukum, 2018)
Legally Normative based on article 18 of the 1945 Constitution and Act Number 6 of 2014 and all Regulations of PDT and Transmigration Village Ministers in relation to Village and Village Funds in Ponngok Village in the Utilization of Village Funds from 2015 to 2017 are in accordance with governmental rules 40% for Community Empowerment and 60% Infrastructure Development.So the Village Fund Year 2018 utilized for the Development of Tourism Area with Aikon: Water Warm Remixâ€ Pilot Village. This Research with study of SWOT analysis with the Statute Approach and Concept Approach found Strenght, Weakness, Opportunity and Threat in Ponggok Village. In accordance Permendesa Number 19 of 2017 contains about the BUMDes Superior Program that can be funded with the Village Fund at point I namely the establishment and development superior product Village and / atau seed of rural areas, among athers, at point d) Village Tourism Industry. The conclusion that the Village has been running well, in accordance with the target, the management becomes the guideline for the Village Fund the following year, the number of investors to cooperate in Ponggok Village as a tourist village that will lead to Pilot Village. With the concept of the researcherâ€™s proposal is Aikon Tourism Area Design: â€œWater Warm Remixâ€ Relaxation Therapy. Keyword: Utilization of Village Fund, Tourism Development, Water Warm Remix, Pilot Village